Family Protective Factors as the Basis for Helping Children With Special Needs Increasing Resilience - Wiwin Hendriani (The Center for Disability Studies and Services Brawijaya University, 2017)
The number of children with special needs which tend to increase have not been followed by the enhancement on people's knowledge and understanding on their developmental characteristics. Discrimination upon these children come not only from other people in their environment but also often from their own families. In this stressful situation, they are possibly having a lot of difficulties in following educational program and enhancing their academic, social and other life skills. The important aspect that makes some of them adaptive in facing adversity or stressful condition is resilience. The aim of this study was describing family protective factors that can be used as the basis for helping children with special needs increasing their resilience. This study used qualitative approach. Participants consist of four families that have child with special needs. All of those families reside in Surabaya. Data were collected through interview with each family member, observation with general guidance and field notes. Thematic analysis was used as data analysis technique. Eight protective factors found as the result of this study: (1) Family independence; (2) Patience and sincerity in experiencing the problems; (3) The persistence; (4) Positive communication; (5) Togetherness and support among family member; (6) Other social support; (7) Activeness in accessing information and openness to situational changes; (8) Similarity positive respond between parents. The paper concludes with a discussion of these findings, as well as explanation about steps that can be taken by parents in strengthening the protective factors, which will support childrens with special needs to increase their resilience.